Position of Consignment in Land Acquisition Whose Whereabouts Are Unknown - Djokdja, Dwiky Oryza; Laturette, Adonia Ivone; Radjawane, Pieter (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Consignment as an act of depositing compensation is contained in Article 1 paragraph (9) of the Supreme Court Regulation Number 2 of 2021 and compensation in court is also explained in the Civil Code in Article 1404 of the Civil Code.Purposes of the Research: The purpose of this study is to examine the position of consignment in land acquisition where the whereabouts of the heirs are unknown. This study helps in seeing the procedures and position of consignment in land acquisition for heirs whose whereabouts are unknown.Methods of the Research: The research method used in this writing is normative research methods. Thus, this research collects data using library research, namely in the form of scientific materials such as legislation, books, official documents, publications and research results.Findings of the Research: Based on the applicable regulations, the position of the consignment where the position of the consignment that has been entrusted by the land acquisition committee to the district court against the owner and heirs who are unknown or the owner and heirs whose whereabouts are unknown is the full right of those who are unknown so that the consignment must be kept until the owner or heirs appear, so that if the owner and heirs do not appear for a long time it will not change the position of the consignment because it has become the full right of the owner and heirs.